Penerapan Fuzzy Analytichal Hierarchy Process untuk Pemilihan Alternatif Solusi Pengurangan Bullwhip Effect - Ilyas Mas'udin (Department Industrial Engineering, University of Muhammadiyah Malang, 2008)
Weaken information and coordination stream between company and enchain its generate information distortion which one of them in the form of ever greater request amplification channel upstream compared to named channel downstream with phenomenon of bullwhip in this research will be conducted development of solution alternative to lessen effect bullwhip by applying method of Fuzzy Analytical Hierarchy Process, where later will be obtained and weight of ranking priority and also get chosen solution alternative to lessen the happening of effect bullwhip. Target of which wish to be reached from this research to determine criterion weight and solution alternative reduction of effect bullwhip and also chosen solution alternative to get lessen effect bullwhip [at] company chain supply. Result which is obtained from measurement of Bullwhip Effect at Supply Chain in CV. Welirang Tirta Mandiri is UD Putra Sejati equal to 1.26, UD Semeru equal to 2.09, Sumber Rezeki shop equal to 1.81, Pacific Shop equal to 2.57, UD. Prima equal to 1.26 while at manufacture echelon equal to 1.56 and retailer echelon 1.26. Chosen alternative to lessen effect bullwhip is to conduct monitoring to inventory level exist in channel downstream (Retailer).